2005
DOI: 10.1093/cercor/bhi027
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Connections Made by Presynaptic Cortico-Cortical Pyramidal Cells in Layer 6 of the Neocortex

Abstract: Paired intracellular recordings with biocytin labelling were made in slices of adult rat somatosensory and visual cortex and in cat visual cortex to examine the properties of synaptic connections made by layer 6 pyramidal cells, to determine whether cortico-cortical pyramids more commonly provide input to other layer 6 pyramids than cortico-thalamic cells, and whether these connections exhibit paired pulse and brief train depression. Pyramidal cells with cortico-cortical like morphology were 2-4 times more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
110
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 25 publications
17
110
1
Order By: Relevance
“…Synaptic connection selectivity between pyramidal cell subtypes Pyramidal cells are functionally connected with each other by local collaterals (Thomson and Deuchars, 1994;Markram et al, 1997;Mercer et al, 2005), and pyramidal cells in different layers are selectively connected (Thomson and Bannister, 2003;Feldmeyer et al, 2005). Pyramidal cells in the same layer appear to be connected in nonrandom ways Song et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic connection selectivity between pyramidal cell subtypes Pyramidal cells are functionally connected with each other by local collaterals (Thomson and Deuchars, 1994;Markram et al, 1997;Mercer et al, 2005), and pyramidal cells in different layers are selectively connected (Thomson and Bannister, 2003;Feldmeyer et al, 2005). Pyramidal cells in the same layer appear to be connected in nonrandom ways Song et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the interlaminar connectivity of pyramidal cells, the reverberating excitation could occur in individual cortical layers (Thomson and Morris, 2002), perhaps within layer V (Sanchez-Vives and McCormick, 2000). Although the specific synaptic connectivity of cortical projection neurons within the same layer is not yet established, recent data suggest that different classes of cortical neurons within a layer may show selective connectivity (Mercer et al, 2005), a finding that has important implications for our understanding of the function of the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary analysis suggested that the firing properties of the layer VI pyramidal neurons in rat could be a useful criterion to predict which neurons were likely to have nicotinic currents, as shown in Figure 2. Recent work has suggested that corticothalamic layer VI neurons are regular spiking neurons (West et al, 2006), whereas layer VI corticocortical neurons tend to be burst-spiking neurons (Mercer et al, 2005). Therefore, we compared nicotinic inward currents between regular spiking and bursting neurons from rats from ages P15 to P42.…”
Section: Nicotinic Currents In Layer VI Pyramidal Neurons Change Acromentioning
confidence: 99%
“…Examination at the electron microscopic level revealed that this axon made asymmetrical synapses, as shown in the bottom left micrograph where a labeled axon terminal (a) synapses with an unlabeled dendritic spine (sp) exhibiting a postsynaptic density (arrow). (Mercer et al 2005). Finally, the neurons shown in Figs.…”
Section: Characterization Of Vglutϩ/gadϩ Nonpyramidal Neurons From Lamentioning
confidence: 99%
“…Nurr1 is expressed in layer VI neurons projecting to the ipsilateral cortex, but not those projecting to contralateral cortical regions (Arimatsu et al 2003). Although functional studies have established the existence of excitatory nonpyramidal spiny neurons in layer VI (Mercer et al 2005), the proportion of polymorphic layer VI nonpyramidal neurons displaying a glutamatergic phenotype has not been thoroughly investigated. Furthermore, relatively few reports describe the electrophysi-ological properties of layer VI spiny nonpyramidal neurons (Brumberg et al 2003;Karayannis et al 2007;Mercer et al 2005;van Brederode and Snyder 1992).…”
Section: Introductionmentioning
confidence: 99%